IN VITRO ANTIBACTERIAL ACTIVITY OF AQUEOUS EXTRACT OF CRANBERRY (VACCINIUM MACROCARPON) AGAINST E. COLI ISOLATED FROM URINARY TRACT INFECTION - Ghulam, Ruqayyah Hussein Kazim; Baniya, Milad Munther Zahid; nema, Adyan abd Al_khalq aziz; Edam, Messad Hammad Kadhim; Thaher, Muslim Hakim Nahi (Journal of Medical Genetics and Clinical Biology, 2024)
The present study was carried out to investigate in-vitro antibacterial activity of aqueous extract of Cranberry (Vaccinium macrocarpon) fruit against Escherichia coli isolated from urinary tract infection. The present study included two experiment; the first one is isolate and identify of E. coli; the second experiment include study in-vitro antibacterial activity of aqueous extract of Cranberry, consisting two steps, the first step involved collection of Cranberry fruit then they were identified and then squeezed by an electric mixer to obtain the aqueous extract. The fruit extract then dried. The second step was to study the in vitro antibacterial activity of Cranberry aqueous extract including minimum inhibitory concentration (MIC) against E. coli used as reference antibiotics. The yielding percentage of Cranberry (Vaccinium macrocarpon) fruit extract was (30%). The in-vitro antibacterial study showed the Cranberry aqueous extract was more effective than Gentamicin against E.coli, this organism was quite resistant to Ciprofloxacin. It could be concluded however that Cranberry aqueous extract was more effective in comparison with the standard antibacterial agent, and that the antibacterial activity of Cranberry aqueous extracts against urinary tract infection may be attributed to its essential particularly the important phenolic compound (Proanthocyanidin).